LANGUAGE ARRANGEMENT AND GLOBALIZATION OF WORLD LANGUAGES WITH A SPECIAL EMPHASIS ON NIGERIA (Ref No 556) - Nwodo, Mary Ngozi (PEOPLE: International Journal of Social Sciences, 2010)
Motivation: This millennium constitutes an important context for any analysis or any intervention in policies of language at the level of states and regions and globally worldwide. Objectives:The objectives of this work were to examine the concepts of expansion or limitation of language planning and language policy and the scope of such concepts in specific linguistic situations such as in Nigeria with international languages. Methodology:It describes the hierarchy and functioning of languages in the world and in Nigeria in particular. It also focuses on the two strongest trends characterizing the current dynamic: the displacement of minority languages as the case in Nigeria and the expansion of English, French and Chinese as the sole world languages. In addition, this article studies the main strategies employed by various actors to oppose these trends, including in particular the representatives of the major national languages such as Igbo, Yoruba, Hausa in Nigeria as an example, whose presence is threatened in several strategic geographical areas. Findings: The reinforcement of local languages weakens national languages that are obstacle for the expansion of English. The reverse is observed in Nigeria where minority languages are not revitalized and where only major languages are thought in schools therefore neglecting minority languages and as a consequence reinforcing the expansion of English. This tendency can only be reversed if anything like a major language is wiped out, therefore giving a chance to every language to prosper and this will also help to stop other languages to disappear. Research Outcomes: This study highlights the role of stakeholders and emphasizes the importance of an expanded concept of language planning that takes into account all the competing forces so as to ensure the success of language policies. Future Scope: It is clear that States, families and enterprises learn languages of higher statuses in the hierarchy and this explains the progress and the expansion of the English circle but also of other super central languages such as Spanish but more importantly the new attractive pole which is Mandarin but also Nigerian languages.